Implementasi Program Keluarga Harapan (PKH) dalam Penanggulangan Kemiskinan: Studi di Desa Kedung Rejo, Kecamatan Waru, Kabupaten Sidoarjo, Provinsi Jawa Timur - Daniar Ajeng Argandini; Radjikan Radjikan; Muhammad Roisul Basyar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Family Hope Program (PKH) is a social protection policy aimed at reducing poverty through conditional cash transfers to low-income families. This study analyzes the implementation of PKH in Kedungrejo Village, Waru District, Sidoarjo Regency, using a descriptive qualitative approach and the policy implementation theory by Van Meter and Van Horn. The findings indicate that the implementation of PKH has been effective, as seen in the implementers’ understanding of the program, inter-agency communication, and stable socio-political support. However, challenges remain, including delays in fund disbursement, limited technical capacity at the sub-district level, and public dissatisfaction with beneficiary data validation. Therefore, the study recommends a more structured disbursement schedule, improved technical capacity of implementers, and the involvement of community leaders in the data collection process to ensure better targeting and sustainability of the program.